PROBLEMATICS OF PAROLE FOR COMMUNITY STUDENTS IN THE PEKANBARU CLASS II SPECIAL CHILDREN'S DEVELOPMENT INSTITUTION - Manihuruk, Tri Novita Sari; Daeng, M.Yusuf; Johar, Olivia Anggie (LPPM, Universitas Muhammadiyah Riau, 2024)
Children who are undergoing guidance at a special children's institution (LPKA) have the right to receive conditional release as long as the terms and conditions are met in accordance with the law. The problem formulation in this research is what are the problems and efforts in granting conditional release to students at the Pekanbaru Class II Special Development Institution for Children. This research method is sociological legal research. The results of the research show that the problems found are that there are no guarantors for students to apply for conditional release, paperwork for submitting administrative documents is still progressing slowly, students violate disciplinary laws, and there is no desire for students to apply for conditional release. The efforts include finding/contacting the Guarantor's family, collaborating well with related parties to make the proposal process easier, carrying out regular independent training to increase officers' knowledge of the applicable rules.